Comparing adsorption performance of microfibers and nanofibers with commercial molecularly imprinted polymers and restricted access media for extraction of bisphenols from milk coupled with liquid chromatography - Kholová, Aneta; Lhotská, Ivona; Erben, Jakub; Chvojka, Jiří; Švec, František; Solich, Petr; Šatínský, Dalibor (Talanta, 2023)
Advanced solid phase extraction (SPE) fibrous sorbents including polyethylene, polypropylene poly (hydroxybutyrate), and polyamide 6 nanofibers, polycaprolactone microfibers/nanofibers, polycaprolactone microfibers/polyvinylidene difluoride nanofibers, and poly (hydroxybutyrate) microfibers/polypropylene microfibers composites, as well as commercial molecularly imprinted polymers and restricted access media sorbent were compared in terms of bisphenols extraction from milk and their clean-up efficiency. Three on-line SPE-HPLC methods were completely validated for the extraction and detection of bisphenols A, AF, C, A diglycidyl ether, and F diglycidyl ether in bovine milk. Polycaprolactone composite nanofibers compared favorably to restricted access media, enabled excellent clean-up of bisphenols from the proteinaceous matrix, and yielded recoveries 98.0-124.5% and 93.0-115.0%, respectively, with RSD less than 10%. Total analysis time including on-line SPE step lasted only 12 min, which represents a significant reduction in time compared with previously reported as well as official European Union and AOAC methods defined for the determination of bisphenols in various matrices.
Keywords: ethery; Animals; Solid Phase Extraction; nanovlákna; Molecularly Imprinted Polymers; Adsorption; hydroxybutyráty; vysokoúčinná kapalinová chromatografie; Nanofibers; Milk; molekulárně imprintované polymery; Chromatography, High Pressure Liquid; Polypropylenes; molekulový imprinting; extrakce na pevné fázi; Ethers; polypropyleny; mléko; zvířata; Hydroxybutyrates; adsorpce; Molecular Imprinting